Thermodynamic analysis of MnWO4 as an oxygen carrier in a chemical looping scheme for hydrogen production - López Van Der Horst, Juliana (2024)
In the last few years, hydrogen has attracted much attention because of its importance in the transition to a sustainable energy system and its use as a raw material in many industrial processes. In this context, chemical looping is proposed as an alternative to traditional methane reforming processes, where methane is partially oxidized by the lattice oxygen of a solid oxygen carrier instead of using water or pure oxygen. This work presents a thermodynamic analysis of MnWO4 as an oxygen carrier and the compositions at equilibrium were calculated by minimizing the total Gibbs free energy of the system. To evaluate its possible integration into a chemical looping scheme, this study assesses the optimal reaction temperature and reactant molar ratio to attain high hydrogen yield while avoiding carbon formation. The findings suggest that temperatures exceeding 775◦C and ratios above stoichiometry are necessary. For successful regeneration, air or water can be used. In the former case a stoichiometric ratio of 1.5:1 of O2 to MnO/W is required, while for the latter, an excess of water in necessary.